2018
DOI: 10.15171/ps.2018.47
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Flavonoids from the Aerial Parts of Stachys lavandulifolia Vahl

Abstract: Background: Stachys lavandulifolia Vahl is a herbaceous plant distributed in the west and south western Asia. Despite of the wide medicinal uses, there are some reports on toxicity potential of this plant. In present study we attempted to evaluate the toxicity and to characterize the cytotoxic principles of S. lavandulifolia. Methods: Brine shrimp lethality test (BSLT) was used to evaluate the general toxicity of the extracts and essential oil obtained from the aerial parts of S. lavandulifolia. Phytochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…In Iran, several species are applied as traditional therapeutic agents in various conditions, including S. acerosa [ 31 ], S. fruticulosa [ 32 ], S. byzantina (known in Farsi as “lamb’s ear” or “lamb’s tongue” or “sonbolehe noghrehi” or “zabanehe bare”) [ 33 , 34 , 35 ], S. inflata (local names; ′′poulk′′ or “Ghol-e-Argavan”) [ 31 , 36 , 37 ], S. lavandulifolia (known as “Chaaye Koohi”) [ 12 , 13 , 31 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], S. pilifera [ 31 , 45 ], S. schtschegleevii [ 32 , 34 , 46 ], S. sylvatica [ 47 ] and S. turcomanica [ 34 ]. Of considerable interest, S. sylvatica (common name “hedge woundwort”) is recommended for the treatment of women with polycystic ovary syndrome (PCOS) [ 47 ].…”
Section: Traditional Medicinal Uses Of Genus Stachysmentioning
confidence: 99%
See 2 more Smart Citations
“…In Iran, several species are applied as traditional therapeutic agents in various conditions, including S. acerosa [ 31 ], S. fruticulosa [ 32 ], S. byzantina (known in Farsi as “lamb’s ear” or “lamb’s tongue” or “sonbolehe noghrehi” or “zabanehe bare”) [ 33 , 34 , 35 ], S. inflata (local names; ′′poulk′′ or “Ghol-e-Argavan”) [ 31 , 36 , 37 ], S. lavandulifolia (known as “Chaaye Koohi”) [ 12 , 13 , 31 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], S. pilifera [ 31 , 45 ], S. schtschegleevii [ 32 , 34 , 46 ], S. sylvatica [ 47 ] and S. turcomanica [ 34 ]. Of considerable interest, S. sylvatica (common name “hedge woundwort”) is recommended for the treatment of women with polycystic ovary syndrome (PCOS) [ 47 ].…”
Section: Traditional Medicinal Uses Of Genus Stachysmentioning
confidence: 99%
“…Regarding the cytotoxicity, the specific extract didn′t demonstrate any activity in K562, SH-SY5Y and Caco-2 cell lines, even at the highest concentrations (1.0 mg/mL). The cytotoxic activity of extracts and isolated flavonoids from the aerial parts of S. lavandulifolia were studied by Delnavazi et al (2018) through the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay [ 13 ]. The dichloromethane extract showed the highest cytotoxic activity in brine shrimp lethality test (BSLT) (LD 50 = 121.8 ± 5.6 μg/mL), while as a positive control was used podophyllotoxin (LD 50 = 3.1 ± 0.6 μg/mL).…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 There are some reports in the literature on phytochemical constituents of various extracts of S. lavandulifolia in literature. [16][17][18][19][20] Four phenylethanoid glycosides including lavandulifoliosides A and B, verbascoside, and leucosceptoside A, together with one iridoid glycoside named 5-allosyloxy-aucubin have been isolated from the aerial parts of S. lavandulifolia by Delazar et al. 16 In another study, acetyl-and butyryl-Cholinesterase and tyrosinase inhibitory activity of different extracts of S. lavandulifolia were assessed and monomelittoside, melittoside, stachysolone and arbutin were isolated and reported as its major compounds.…”
Section: Introductionmentioning
confidence: 99%
“…17 Recently, Delnavazi et al reported the isolation of eight methoxylated flavonoids from chloroform extract of this species, of which chrysosplenetin, kumatakenin and viscosine were found to have higher preferential toxicity against MDA-MB-23 cells in comparison with tamoxifen. 18 The present study was an attempt to more investigate phytochemical constituents of this medicinal species, specially its flavonoid glycosides content using various chromatographic and spectroscopic methods.…”
Section: Introductionmentioning
confidence: 99%